HUBUNGAN EFIKASI DIRI DENGAN KEPATUHAN MINUM OBAT PADA PASIEN TBC DI WILAYAH KERJA PUSKESMAS PARONGPONG KECAMATAN PARONGPONG KABUPATEN BANDUNG BARAT - Mella Yusef Fintiya; Imanuel Sri Mei Wulandari (Jurnal Skolastik Keperawatan, 2019)
Tuberculosis is a pulmonary infectious disease caused by Mycobacterium Tuberculosis. In Indonesia tuberculosis case every year is increasing. Indonesia kept the 6th highest tuberculosis sufferer in the world, while West Java kept the first order. The purpose of this research is to see the relationship of self-efficacy with the adherence of OAT medication. The research method uses a correlational descriptive design with a cross sectional approach by involving 23 respondents undergoing treatment at a parongpong Puskesmas, the respondent chosen using the Purposive sampling. Independent variables are self-efficacies, variable dependent is the adherence to taking medication. The instrument in this study is a questionnaire analyzed using Pearson's R. Results and analysis of self-efficacy by taking compliance the drug has a relationship with the value of P-value 0.030 or (P ≤ 0.05) with a moderate relationship level (0.454). Efficacy is one of the factors that affects the adherence to the treatment of patients with tuberculosis in the working area of Parongpong Puskesmas. Suggestions for further research need to know the role of health cadres in the compliance with medication.